RETRACTED: Determinants Information Disclosure And Responsibility of Financial Statements to Consistency Muzakki - Arwani, Agus (EQUILIBRIUM, 2021)
The purpose of the research was to decide the impact of data revelation and money-related articulation responsibility on the consistency of paying zakat, infaq, and sadaqah on LAZ in Pekalongan city. This study uses a quantitative approach that utilizes a questionnaire distributed to s 117respondent. The comes about of the think about appearing that data divergence had a critical impact on the consistency of paying zakat, infaq and sadaqah in Pekalongan city as prove by the calculated t esteem more noteworthy than the t table esteem and the noteworthiness esteem underneath 0.05 so that the first hypothesis Ha1 was accepted. Likewise, the accountability variable financial statements also affect the consistency of paying zakat partially tested to receive Ha2. The simultaneous testing that the effect of information disclosure and financial accountability on the consistency of muzakki also influences simultaneously, which is indicated by the F value greater than the F table. The research finding is that information disclosure, and accountability of financial statements have a partial and simultaneous effect on the consistency of paying for ZIS in the usual city of Pekalongan. The originality of research can be seen from the disclosure of information and the responsibility of financial statements to create consistent muzakki paying zakat, which is different from previous research. The practical implication of this research is that amil zakat institutions can use the importance of disclosing information and accountability of financial statements to be more consistent in entrusting their zakat.